Adjacency Tree Families and Complementarity Criteria - Maksimov, Anatoliy G.; Zavalishin, Arsenii D.; Abramov, Maxim V.; Tulupyev, Alexander L. (Computer Tools in Education, 2020)
The article discusses the properties of families of minimal joint graphs. The concept of non-extenuating paths of graphs is introduced. The criterion of additionality for families of backbone connected graph trees is formulated and proved. Theoretical and practical significance lies in the study of structures that will be best suited for working with algebraic Bayesian networks and, thus, become one of the goal of their machine learning. We note the novelty of looking at the problem, or rather, studying the question for which families of graphs there is a set of loads, the family of MGS over which exactly coincides with the given one.